Exploring Drivers and Barriers of Fossil Fuel Subsidy Reforms in Developing Countries: A Literature Review - Abderrahman SADDIKI; Asmaa CHAOUTI (Communications of International Proceedings, 2021)
While all the countries around the world agree to the urgency of eliminating fossil fuel subsidy reforms due to the rising awareness of their environmental, economic, and social effects, the magnitude of fossil fuel subsidies remains substantially high. Efforts of reforms of fossil fuel subsidies were aborted in many developing countries. It is, therefore, of particular importance to identify and examine the motivators and obstacles of fossil fuel energy reforms in those countries. This study conducted research limited to peer-review papers published between 2000 and 2020. Rather than offering a comprehensive summary of all the factors that motivate or hinder subsidy reforms in an exhaustive way, we structured evidence collected into five categories of factors: economic, social, environmental, political, and institutional. Our research focuses on developing countries as the largest part of fossil fuel subsidies are embedded in non-democratic countries with weak institutional and political systems. Key drivers included fiscal strain on the governments; economic cost of fossil fuel subsidies, the role of international oil prices, environmental cost, international commitments, donor pressure, and social inequity. Key barriers included lack of communication to the public, lack of credibility and confidence in governments, weak macroeconomic conditions, welfare implications on the poor and households, the burden from powerful interest groups, and institutional capacity of governments. Our findings show that ensuring successful implementation and durability of fossil fuel reforms will require a full understanding of a country’s economic, social, political, and institutional conditions and constraints.
Keywords: Subsidies; Fossil Fuels; Energy; Government Support.